Concentrations of luteinizing hormone and ovulatory responses in dairy cows before timed artificial insemination - Stephanie Leeann Pulley; D. H. Keisler; Scott L. Hill; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2013)
The objective of this study was to determine the incidence of spontaneous and gonadotropinreleasing hormone (GnRH)-induced surges of luteinizing hormone (LH) and ovulatory responses in lactating dairy cows enrolled in a timed artificial insemination (TAI) protocol. Cows (n = 70) in a single herd were assigned to one of two presynchronization protocols: Pre- 10 or PG-3-G. Cows assigned to the Pre-10 treatment received 2 injections of prostaglandin F2α(PGF2α) 14 days apart (Presynch), with the second injection administered 10 days before the onset of a TAI protocol. Cows assigned to the PG-3-G treatment received an injection of prostaglandin F2α(PGF2α), then 3 days later an injection of GnRH (GnRH-1) 7 days before the onset of a TAI protocol. All cows received the first GnRH injection (GnRH-2) of the Ovsynch protocol and a PGF2αinjection 7 days later, then cows received the breeding injection of GnRH (GnRH-3) at either 56 or 72 hours after PGF2α, with insemination occurring 12 to 16 hours after the second GnRH injection. Blood samples were collected during the study to monitor serum changes in LH, progesterone, and estradiol to determine why ovulatory responses to GnRH-induced LH release did not approach 100% when follicle dominance and adequate follicle size was achieved. Presynchronization administration of GnRH-1 increased the incidence of LH surges and ovulation rates in cows presynchronized with PG-3-G compared with Pre-10. Incidence of ovulation and occurrence of LH surges did not differ after GnRH-2, but more LH was released in Pre-10 than PG-3-G cows. Luteolysis, LH surge incidence, and ovulation rates were similar among the 4 treatment-time combinations after GnRH-3. Pregnancy per TAI was decreased in Pre-10 at 56 hours compared with Pre-10 at 72 hours and PG-3-G at 56 and 72 hours. We concluded that administration of GnRH 56 hours before breeding decreased pregnancy per TAI compared with administration of GnRH at 72 hours when cows were presynchronized with Pre-10. Presynchronization with PG-3-G resulted in acceptable pregnancy per TAI with GnRH administration occurring at either 56 or 72 hours before TAI. The flexibility of GnRH timing with the PG-3-G presynchronization protocol may be an advantage compared with the Pre-10 protocol for dairy cattle when programmed for a TAI at first service.; Dairy Day, 2013, Kansas State University, Manhattan, KS, 2013; Dairy Research, 2013 is known as Dairy Day, 2013
Keywords: Dairy Day; 2013; Kansas Agricultural Experiment Station contribution; no. 14-179-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 1093; Follicle; Ovsynch; Presynchronization; Timed AI